Wood identification in objects of Bambuti people from the Congo in the collection of the Slovene ethnographic museum - Katarina Čufar; Hans Beeckman; Marko Frelih; Luka Krže; Wannes Hubau; Maks Merela (Les)
The African collection of the Slovene Ethnographic Museum (SEM) in Ljubljana, Slovenia, holds objects of everyday life from the Bambuti people from the Ituri forest, in the northeastern part of the Democratic Republic of the Congo. The items were collected by the anthropologist Paul Joachim Schebesta, possibly during his expeditions around 1930. The objects containing wood were selected for wood identification by using microscopic wood identification, with the help of the InsideWood database and reference samples from the xylarium of the Royal Museum for Central Africa in Tervuren, Belgium. The investigated musical instrument, a wooden zither, was made of wood of Musanga cecropioides, the handle of the shield of Alstonia sp., the dagger and sheath of Autranella congolensis or another high density species of Sapotaceae, and the crossbow of Nauclea diderichii (bow) and Xylopia sp. (stock). Wood identification helped us to gain additional information on the origin, knowledge of wood, and time of the collection of objects in the Congo.